A 7-Year Lag Precipitation Teleconnection in South Australia and Its Possible Mechanism - Fan, Lingli; Guan, Huade; Cai, Wenju; Rofe, C. P.; Xu, Jianjun (Frontiers in Earth Science, 2020)
Precipitation teleconnections with large-scale ocean-atmosphere oscillation systems provide useful information for water management. Here we present a seven-year lag response in South Australia (SA) precipitation to the Southern Annular Mode (SAM) in a positive Interdecadal Pacific Oscillation (IPO) phase. This teleconnection between a positive SAM phase and increased SA precipitation, and vice-versa, statistically consists of three sequential steps : a 27-season lag positive correlation between sea subsurface potential temperature (SSPT) to the south of SA and SAM; a zero-season lag positive correlation between sea surface temperature (SST) and SSPT; and a 2-season positive lag correlation between SA precipitation and SST. Physically, this teleconnection seems to be associated with a supergyre circulation of the Southern Hemisphere Oceans, which transfers SAM signal via subsurface potential sea temperature in the central south Pacific to the south of SA in 27 seasons during the positive IPO phase. Practically, this teleconnection provides a 7-year-lead drought precursor for rain-fed agriculture planning in South Australia. However, the teleconnection disappears in negative IPO phases. The oceanic pathway via the supergyre suggested in this study provides a basis to predict when this seven-year teleconnection may resume in the future based on observation and/or modelling.